(untitled) (Economic and Political Thought, 2019)
The work focuses on the analysis of the 2015 citizens’ legislative initiative “Stop Abortion” and gives a careful thought to this instrument in the light of the assumptions of the theory of liberal democracy. I reconstruct the circumstances of the legislative initiative, its political, social and cultural context and the discussion on the project in the Sejm. A citizens’ legislative initiative (CLI) as a new democratic instrument was intended to be a response to problems and deficiencies of democracy in Poland, an idea to make social and political life democratic by increasing general activeness of citizens and their participation in taking state decisions. I analyse the CLI of “Stop Abortion” as a project activating a broad, individual and organised, citizens’ initiative in the “world of life” and if it meets the requirements of participative democracy. Political actors treat this big social and cultural capital gathered around the initiative “Stop Abortion” in an instrumental way. The discussion on the “Stop Abortion” project in the Sejm is a denial of the requirements of deliberative democracy. Simply speaking, the initiators of “Stop Abortion” impose their subjective point of view on the state, which they want to use as a tool in popularising their views as legally binding rules, which is in conflict with values and endangers the foundations of liberal democracy. It is also an indication of degradation of public language and political communication.